Functional properties of a phenylalanine ammonia-lyase promoter from Arabidopsis. - Ohl, S (1990)
Phenylalanine ammonia-lyase (PAL) is encoded by a small family of genes in Arabidopsis. We cloned and partially characterized one of these genes, PAL1. The deduced amino acid sequence is highly similar to PAL from bean, parsley, and rice. The promoter contains sequence elements homologous to two putative regulatory elements conserved among several phenylpropanoid genes. The regulation of the PAL1 gene was examined by analysis of beta-glucuronidase (GUS) activity in transgenic Arabidopsis containing PAL1-GUS gene fusions. The PAL1 promoter was activated early in seedling development and in adult plants was strongly expressed in the vascular tissues of roots and leaves, but was not active in the root tip or the shoot apical meristem. In flowers, expression was observed in sepals, anthers, and carpels, but not in petals. Transcripts encoded by the endogenous PAL genes and GUS transcripts from the PAL1-GUS gene fusion were induced by wounding, HgCl2-stress, and light. Analysis of the regulatory properties of 5' deleted promoters showed that the proximal region of the promoter to -290 was sufficient to establish the full tissue-specific pattern of expression and that the proximal region to -540 was responsive to environmental stimuli. Negative and positive elements were located between -1816 and -823 and between -823 and -290, respectively.